2019
DOI: 10.2147/jmdh.s198024
|View full text |Cite
|
Sign up to set email alerts
|

<p>Facilitation of activities for people with dementia in day care: a qualitative study exploring the experiences of staff</p>

Abstract: Background: Day care service (day care) is recommended as an activity service for home-dwelling people with dementia in Norway. However, there is limited knowledge about strategies to promote engagement and participation in activities at day care. The aim of this study was to gain understanding of the staff’s experiences on how to enhance engagement and participation in activities for attendees. Methods: The study has a qualitative design, using group interviews with staff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, the level of engagement at both types of day care found in our study supports Strandenæs et al. (2019) finding that regular day care attendees had a generally high level of engagement. The two types of day care, therefore, seem to provide attendees with activities that create engagement in line with the overall aim of such services.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the level of engagement at both types of day care found in our study supports Strandenæs et al. (2019) finding that regular day care attendees had a generally high level of engagement. The two types of day care, therefore, seem to provide attendees with activities that create engagement in line with the overall aim of such services.…”
Section: Discussionsupporting
confidence: 90%
“…Even though day care services are organised differently than long‐term residential care, they are often situated in the same institutional environment. Strandenæs, Lund, and Rokstad (2019) study of day care services found that even though staff talked about the importance of getting to know the attendees to provide tailored activities and meaningful days, no examples of this was found in observations of attendees. Staff also expressed that there was too much focus on attendees’ limitations indicating that there is a potential to offer more differentiated and tailored day care services (Strandenæs et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, some day care alternate attendees of different ages and functional levels to different activities or days for more homogenous groups. When there is a progression in dementia or behavioural problems occur, day care is often no longer considered a suitable service (Strandenaes et al., 2019). Day care is traditionally and most commonly established in an institution like a nursing home or in centres offering services for older adults (Gjøra et al., 2015; Taranrød & Strandli, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…18,21 However, most activity interventions for people living with dementia were facilitated by nursing or care staff, researchers, or others (e.g., volunteers, musicians, clowns). While the presence of a facilitator can promote uptake of, and engagement in, meaningful activities by people living with dementia in LTC, 22 questions have been raised about the effectiveness of the activity interventions being confounded by the social contact with or person-toperson attention received from the facilitator, making it unclear and difficult to determine which element (i.e., the activity or the facilitator) has contributed most to the intervention effect. 18 This means that it is difficult to delineate the 'real' effect of the activity interventions being introduced to people living with dementia, as any positive effect found may either be mediated and/or inflated by their interaction with the facilitator.…”
Section: Introductionmentioning
confidence: 99%